Organic geochemical characteristics and organic matter enrichment of mudstones in an Eocene saline lake, Qianjiang Depression, Hubei Province, China. (April 2020) - Kong, Xiangxin; Jiang, Zaixing; Zheng, Youheng; Xiao, Meng; Chen, Chen; Yuan, Hao; Chen, Fengling; Wu, Shiqiang; Zhang, Jianguo; Han, Chao; Liu, Shengqian
Abstract: The Qianjiang Depression is a typical Eocene hypersaline lake basin developing good source rocks in the Qianjiang Formation, which have recently been identified as a potential target for saline lacustrine shale oil exploration. Previous studies have only focused on estimates of source rock potential and reservoir quality. However, studies on organic matter enrichment mechanisms in evaporative environments are limited. Based on organic geochemical and mineralogical data, as well as sedimentological analyses, we researched the factors controlling differences in organic matter enrichment in the basin. The results show that total organic carbon (TOC) contents are closely associated with lithofacies with distinct variations. Three main lithofacies associations (LAs) were identified: (1) glauberite-rich LA1 with medium TOC; (2) carbonate-rich LA2 with high TOC; and (3) anhydrite-rich LA3 with low TOC. The distribution of biomarkers from 14 samples indicate both higher land plants and aquatic organisms were involved in the organic matter accumulations. Combining experimental results on gammacerane/C30 hopane, extended tricyclic terpane ratio (ETR), Sr/Ba, V/Ni, and sedimentary characteristics, we analyzed the sedimentary environments of the three LAs. LA1 was deposited in a salinity stratified waterbody with strong evaporation, LA2 was deposited in a still, stratified deep waterbody, whereas LA3 was deposited in a disturbed, saline waterbody. Sedimentary environments not only controlled the formation of the lithofacies, but also influenced the organic matter sources and preservation. Relatively low salinity, strong anoxic condition without physical disturbance, appropriate nutritional terrigenous material inputs, and algal blooms produced the best organic matter enrichment in the saline lake system. Highlights: We studied a hypersaline lake rhythmite from the Qianjiang Formation, Hubei, China. Saline lake environments influence organic matter accumulation. Hypersalinity is unfavorable for organic matter enrichment. ETR is a valid biomarker to assess redox conditions in saline lake sediments. High lake levels with anoxic conditions favor organic matter accumulation.